COVERAGE OF SPEECH, COMMUNICATION, READING AND WRITING SKILLS IN THE FIRST STEP CURRICULUM (Spectrum Journal of Innovation, Reforms and Development, 2022)
In this article, the special features, importance and goal tasks of speech, communication, reading, writing skills in the "First Step" educational program, as well as expected results in the areas of small speech and language, fine motor skills of fingers and hands are highlighted.